Giant clam aquaculture in the Pacific region: perceptions of value and impact. Issue 5 (4th July 2018) - Moorhead, Anne
ABSTRACT: Aquaculture of giant clams was developed in the Pacific region in the 1970s and 1980s, linked to community farming and efforts to develop commercial opportunities, particularly high-value exports. Giant clam industries did not develop as expected, but nonetheless many countries still have giant clam aquaculture programmes. Investigations in three countries indicate that giant clams hold other values, notably cultural value, socio-ecological value, value to tourism, and value through building social capital, and these may explain the continuation of the aquaculture programmes. Understanding and adequately assessing local values is a challenge for development investors, who may be missing important impacts from their projects.